Impact of Information Governance and Management As Well As the Associated Technology According to COBIT Framework on the Characteristics of Primary Accounting Information in Jordanian Commercial Banks - Abu Afifa, Malik (Jordan Journal of Business Administration, 2021)
The increasing technological investments in companies, specifically in commercial banks, leads to the adoption of important frameworks in the information governance and management as well as the associated technology, which are issued by international organizations, such as COBIT. COBIT approach preserves information technology, maximizes its benefits, improves its outputs and ensures that the company’s strategic goals are achieved. In this regard, the present study aimed at investigating the impact of information governance and management as well as the associated technology according to COBIT framework on the characteristics of primary accounting information in Jordanian commercial banks. The study used a questionnaire as a research tool and the study population consisted of all Jordanian commercial banks (13 banks). The study used the purposeful sample (managers, heads of departments and heads of units, who are working at the financial department, internal control and audit department, risk management department and information technology department in banks). Two hundred and eighty-six questionnaires were distributed, of which one hundred and seventy-four questionnaires were collected and finally one hundred and seventy-one questionnaires are used for hypothesis testing. The study concluded that information governance and management as well as the associated technology according to COBIT framework affect the characteristics of primary accounting information (relevance and reliability) in Jordanian commercial banks. The study recommended defining organizational relationships and separating jobs in Jordanian commercial banks.